1992
DOI: 10.1038/ki.1992.184
|View full text |Cite
|
Sign up to set email alerts
|

In vitro formation and expansion of cysts derived from human renal cortex epithelial cells

Abstract: Acquired renal cysts derive from terminally differentiated tubular epithelium in adults as a consequence of increased epithelial cell proliferation, fluid accumulation and extracellular matrix remodelling. To understand better how human epithelial cysts may be initiated and progressively expand, cells from primary cultures of normal human adult renal cortex were dispersed in polymerized type I collagen. The transparent matrix permitted repeated observation by light microscopy of cyst formation from individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 30 publications
3
62
0
Order By: Relevance
“…Formation and expansion of "in vitro" cysts, derived from solitary human cortex cells, depends from the coordinated interplay among cellular proliferation, fluid secretion and remodeling of extracellular matrix surrounding cysts (8)(9). The molecular mechanism and the pathogenesis of cyst formation are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Formation and expansion of "in vitro" cysts, derived from solitary human cortex cells, depends from the coordinated interplay among cellular proliferation, fluid secretion and remodeling of extracellular matrix surrounding cysts (8)(9). The molecular mechanism and the pathogenesis of cyst formation are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Ligands for the EGF receptor are EGF, TGF-a, and HB-EGF. Recently, experimental studies have shown that activation of this EGF receptor by binding with the ligands EGF or TGF-a results in cyst formation in vitro (8) and in vivo (9). Inhibition of EGF receptor tyrosine kinase activity blocked tubular cyst formation in an in vitro system (14), blockade of EGF receptor resulted in attenuation of cystic disease in animal models (15,16), whereas ErbB4 knockout mice showed an accelerated cyst progression and renal function deterioration (17).…”
Section: Discussionmentioning
confidence: 99%
“…We included 27 patients with ADPKD who all completed a single-center interventional trial investigating the short-term renal hemodynamic effects of the V2RA tolvaptan that was performed between 2011 and 2013 (8). ADPKD was diagnosed using the modified Ravine criteria (9).…”
Section: Study Design and Populationmentioning
confidence: 99%
See 2 more Smart Citations